Quantitative Evaluation of Visual Function 12 Months after Bilateral Implantation of a Diffractive Trifocal IOL. Issue 6 (December 2015) - Marques, João P.; Rosa, Andreia M.; Quendera, Bruno; Silva, Fátima; Mira, Joaquim; Lobo, Conceição; Castelo-Branco, Miguel; Murta, Joaquim N.
Purpose: To quantitatively evaluate visual function 12 months after bilateral implantation of the Physiol FineVision ® trifocal intraocular lens (IOL) and to compare these results with those obtained in the first postoperative month. Methods: In this prospective case series, 20 eyes of 10 consecutive patients were included. Monocular and binocular, uncorrected and corrected visual acuities (distance, near, and intermediate) were measured. Metrovision ® was used to test contrast sensitivity under static and dynamic conditions, both in photopic and low-mesopic settings. The same software was used for pupillometry and glare evaluation. Motion, achromatic, and chromatic contrast discrimination were tested using 2 innovative psychophysical tests. A complete ophthalmologic examination was performed preoperatively and at 1, 3, 6, and 12 months postoperatively. Psychophysical tests were performed 1 month after surgery and repeated 12 months postoperatively. Results: Final distance uncorrected visual acuity (VA) was 0.00 ± 0.08 and distance corrected VA was 0.00 ± 0.05 logMAR. Distance corrected near VA was 0.00 ± 0.09 and distance corrected intermediate VA was 0.00 ± 0.06 log-MAR. Glare testing, pupillometry, contrast sensitivity, motion, and chromatic and achromatic contrast discrimination did not differ significantly between the first and last visit (p>0.05) or when compared to an age-matched control group (p>0.05). Conclusions: The Physiol FineVision ® trifocal IOL provided satisfactory full range of vision and quality of vision parameters 12 months after surgery. Visual acuity and psychophysical tests did not vary significantly between the first and last visit.